Metamorfose dos centros urbanos: uma análise das transformações na centralidade de João Pessoa PB, 1970- 2006 - Andrade, Paulo Augusto Falconi de (2007)
It was aimed in the present work to investigate the implications of the metamorphosis process in the urban centrality of João Pessoa, capital of Paraíba state, under the point of view of central uses and activities, starting in the 1970s up to present days. In the spatial ambit on which the present work focuses is a central area in João Pessoa. However, it is important to emphasize that references to other sectors of the city will be made, which have become in the last decades new places of the centrality process. The temporal picture, for its turn, follows the transformations that occurred from 1970 to present days, because since those times deep transformations were generated by post-modern paradigms. In fact it is a phase of changes in the intraurban structure of our cities, where selective shopping activities and new way of life emerged under the influences of privileged social classes anxiety in the context of consumerist society. The methodology used here included not only the bibliographical survey performed, whose importance is revealed by the theoretical basis constructed in the present work, but also the analysis of the phenomenon of changes in the centrality, where data and indicators were provided by the Laboratório do Ambiente Urbano e Edificado (Laboratory of Urban and Built Structures Environment) of the Federal University of Paraíba. The main town centre of João Pessoa sprawled predominantly towards the littoral zone along the Avenida Epitácio Pessoa and its surroundings, following the moving tendencies of high profit people. The results obtained here showed that the main town centre of João Pessoa has deteriorated physically with respect to many buildings, and the estate housing dynamics have decreased in relation to new town centres in the city of João Pessoa. However, under the point of view of commercial activities and services available, besides other vital activities for the living process in the area, the traditional town centre of João Pessoa continues to generate profits for the local economy, having the greatest number of licensed activities and a quite expressive amount of money in circulation. Thus, the vitality and urban centrality of João Pessoa town centre, reflected by the great diversity of activities of socio-economical interest is presently clearly evident.